2006
DOI: 10.2353/ajpath.2006.051222
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Attachment of Peritoneal Tumor Metastases to Omental Immune Aggregates and Possible Role of a Unique Vascular Microenvironment in Metastatic Survival and Growth

Abstract: Controlling metastases remains a critical problem in cancer biology. Within the peritoneal cavity, omental tissue is a common site for metastatic disease arising from intraperitoneal tumors; however, it is unknown why this tissue is so favorable for metastatic tumor growth. Using five different tumor cell lines in three different strains of mice, we found that the omentum was a major site of metastases growth for intraperitoneal tumors. Furthermore, initial attachment and subsequent growth were limited to spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
157
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(178 citation statements)
references
References 56 publications
8
157
0
5
Order By: Relevance
“…These results indicate that CCL22/CCR4 may participate in this selective infiltration process (80). Furthermore, milky spots are rich in capillaries and the surrounding vascular density is high (81). CD105 + vessels and vascular sprouts have been also located within milky spots, indicating that angiogenesis is active (81).…”
Section: Milky Spotsmentioning
confidence: 81%
See 1 more Smart Citation
“…These results indicate that CCL22/CCR4 may participate in this selective infiltration process (80). Furthermore, milky spots are rich in capillaries and the surrounding vascular density is high (81). CD105 + vessels and vascular sprouts have been also located within milky spots, indicating that angiogenesis is active (81).…”
Section: Milky Spotsmentioning
confidence: 81%
“…Furthermore, milky spots are rich in capillaries and the surrounding vascular density is high (81). CD105 + vessels and vascular sprouts have been also located within milky spots, indicating that angiogenesis is active (81). Additionally, milky spots also serves as a hypoxic niche, which enhances the self-renewing capacity of gastric cancer stem/progenitor cells regulated by hypoxia-inducible factor-1α (HIF-1α) (82).…”
Section: Milky Spotsmentioning
confidence: 98%
“…Indeed, immunochemical staining of peritoneal biopsies showed that VEGF expression was confined mainly to the mesothelial monolayer (Aroeira et al, 2005;Combet et al, 2000). The mesothelial origin of peritoneal VEGF was ultimately confirmed in an elegant study, during which various cell types were isolated from the peritoneal lavage and the omentum, and analysed by several techniques for the ability to generate VEGF (Gerber et al, 2006). It transpired that omental mesothelial cells were responsible for the majority of peritoneal VEGF produced.…”
Section: Vegf In the Peritoneal Cavitymentioning
confidence: 94%
“…In particular, omental milky spots are composed of numerous macrophage and lymphocyte aggregation and are involved in the clearance of particles, bacteria and tumor cells from the peritoneal cavity [5][6][7][8][9][10][11]. Omental milky spot is a wellknown site of metastases of carcinomas of the ovaries, stomach and colon.…”
mentioning
confidence: 99%